DETERMINANTS OF DEVELOPMENT OF THE INTERNATIONAL SCIENTIFIC AND TECHNICAL COOPERATION IN THE SPACE FIELD WITH RUSSIA`S PARTICIPATION - A. P. Krishtofor (Вестник университета)
The present stage of development of the international scientific and technical cooperation in the space industry has been investigated. The main shifts, happening in the geographical directions of the international scientific and technical cooperation in the space field have been considered. The potential, problems and the prospects of development of the international scientific and technical cooperation in the space field with the CIS countries have been studied. The perspective directions of its development with participation of Russia have been allocated; consequences of imposition of sanctions of foreign countries in the space field on development of scientific and technical cooperation have been analyzed; the role of the countries and regions in realization of strategic priorities of the Russian Federation in development of scientific and technical cooperation has been shown.